EVALUACION CUANTITATIVA DEL SISTEMA FAGOCITARIO DE LA SALIVA EN DIFERENTES ESTADIOS CLINICOS DE INFECCION HIV/SIDA - Taboada, Manuel (1999)
The porcentaje of the results obtained in 32 healthy people and 66 patients evita SIDA,thhou significant diferences: Faces III o IV; II o IV There was no significance statisteis in the control group,in Fase II, in II o III. There is between existant information and the results obtained wita reference to Fase of HIV, stomatology simton with tendence to rigth desviation. (Esquema de Arneth).